The Role of Islamic Values in Prevention of Global Crises - Baydoun, Ibtissam Ibrahim (Journal of Humanities & Social Sciences, 2022)
Our commitment to Islamic values is one of the most crucial means for the prevention of global crises, as they constitute of morals and foundations to which the benefits of humankind in this world and the hereafter are restricted, These values must be planted in the rising generations and the ones to come so that it shields them. They are also the most effective remedy when crises arise. Therefore raising awareness and revealing the true face of crises are a must, And if we delve deeper into the causes of wars and economic, health and social collapses, we will find within that the misrepresentation and twisting of the statements of our religion, extremism in its two forms -excessiveness and negligence- along with indulging in usury (Riba) gambling, and adultery. The younger generations must be persuaded and prompted through wisdom, proof and reasoning to retrieve our brighter past and place it under comparison with this dark present in order for them to get in touch with the reasons that lead to these drastic changes, As there is no doubt that when corruption takes hold of the hearts, it metastasizes in the souls and societies, then values and morals collapse and vanish, and undifferentiating hardships afflict entire societies and multiply in various forms.